The effects of protein supplementation during energy balance and energy restriction on whole body protein turnover and metabolism - Ruddick-Collins, L.C.; King, N.A.; Byrne, N.M. (Proceedings of the Nutrition Society, 2018)
Whole body protein turnover (WBPT) and protein oxidation are metabolically energy costly processes(1) and may contribute to the increased resting and postprandial energy expenditure (EE) on high protein diets(2–4). Sixteen participants (9 M, 7 F) undertook 4 x 2 week study phases; habitual diet 1 (HD1) (subjects consumed their own habitual diet), habitual diet 2 (HD2) (as per HD1), high protein energy balance (HPEbal) (0·5 g/kg/d whey protein supplement, maintaining energy balance) and high protein energy restriction (HPER) (33 % ER with 0·5 g/kg/d protein supplement, protein intake equal to HPEbal). WBPT (end product method, single dose 15N glycine, measured in the fed state(5)), 24hr nitrogen balance, resting and short-term postprandial EE (30–40 and 80–90 min) were measured at the end of each diet phase.